Konsep Wakaf Untuk Diri Sendiri dan Implementasinya: Studi Komparatif Pemikiran Ibnu Taimiyah dan Hukum Wakaf Indonesia: The Concept and Implementation of Self-Endowment (Waqf): A Comparative Study of Ibn Taymiyyah and Indonesian Waqf Law - Diaz Ilyasa (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
This study examines the concept of self-endowment (waqf for oneself) according to the perspective of Ibn Taymiyyah and its relevance to the development of waqf law in Indonesia. This topic is significant because Islamic jurisprudence on waqf still presents differing opinions regarding the permissibility of self-endowment, while Indonesian positive law has not explicitly regulated such a concept. The study aims to analyze Ibn Taymiyyah’s view on self-endowment, examine its regulation within Indonesian waqf law, and explore the possibility of its practical implementation. This research employs a qualitative method with a library research approach, using juridical-normative and comparative analyses. The data were collected through documentation studies by examining various waqf-related sources, including classical fiqh literature, books, academic journals, and statutory regulations, particularly Law Number 41 of 2004 concerning Waqf and Government Regulation Number 42 of 2006. The findings reveal that Ibn Taymiyyah permits self-endowment under certain conditions, provided that the primary objective of waqf is preserved and its benefits remain accessible to others. Meanwhile, Indonesian waqf law does not explicitly regulate this issue, yet it still provides room for interpretation through the concept of family waqf (waqf ahli) and the role of nāẓir. This study is expected to contribute to the development of waqf jurisprudence studies and serve as a conceptual foundation for the advancement of a more flexible waqf legal framework while remaining consistent with sharia principles.